2014
DOI: 10.2175/106143014x14031280668290
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in Groundwater Pollution and Quality

Abstract: Groundwater pollution due to anthropogenic activities may impact overall groundwater quality. Organic and inorganic pollutants have been routinely detected at unsafe levels in groundwater rendering this important drinking water resource practically unusable. Vulnerability of groundwater pollution and subsequent impact has been documented in various studies across the globe. Field studies as well as mathematical models have demonstrated increasing levels of pollutants in both shallow and deep aquifer systems. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, most EOCs are not regulated in the environment or routinely monitored in groundwater (Lapworth et al, 2019). Their properties, environmental behaviour and toxicological effects are still poorly understood (Brack, 2012;Halden, 2015;Kurwadkar, 2014;Lapworth et al, 2019;NOR-MAN, 2019;Pal et al, 2014;Petrie et al, 2015;Poynton and Vulpe, 2009;Sauvé and Mélanie, 2014;Schriks et al, 2010;Stuart et al, 2012;Thomaidi et al, 2015). There are 30,000 to 70,000 registered chemicals in daily-used products (Schwarzenbach et al, 2006), and about 4000 new chemicals are registered every day (Dulio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, most EOCs are not regulated in the environment or routinely monitored in groundwater (Lapworth et al, 2019). Their properties, environmental behaviour and toxicological effects are still poorly understood (Brack, 2012;Halden, 2015;Kurwadkar, 2014;Lapworth et al, 2019;NOR-MAN, 2019;Pal et al, 2014;Petrie et al, 2015;Poynton and Vulpe, 2009;Sauvé and Mélanie, 2014;Schriks et al, 2010;Stuart et al, 2012;Thomaidi et al, 2015). There are 30,000 to 70,000 registered chemicals in daily-used products (Schwarzenbach et al, 2006), and about 4000 new chemicals are registered every day (Dulio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Around the world, several water bodies do not meet the minimum quality standards necessary to ensure their utilization for anthropic activities [1][2][3] and groundwater quality is even declining over time [4]. This phenomenon is attributable to the presence of different pollutants in both surface and groundwater resources [5], due either to anthropogenic activities or natural processes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sources of groundwater contamination due to human activities are widespread and include diffuse sources as well as point-sources of pollution, such as land application of animal manure containing contaminants (e.g., veterinary pharmaceuticals) and agrochemicals in agriculture, leakages from sewers or sanitation systems, from waste disposal sites, landfills, underground storage tanks and pipelines, and accidental spills in mining, industry, traffic, health care facilities and military sites. The exploitation of petroleum products and the development of the industrial chemistry have given rise to a large number of organic chemicals, many of which are found in the environment (Kurwadkar, 2014). Various studies have shown that anthropogenic chemicals such as pesticides (Arias-Estevez et al 2008;Postigo & Barceló, 2015), pharmaceuticals and personal care products (Holm et al 1995;Deo & Halden,…”
Section: Introductionmentioning
confidence: 99%